Meningkatkan Hasil Belajar IPA Metode Team Quiz Berbantuan Media Video Animasi pada Siswa Kelas V di SDN 1 Simo Tahun Pelajaran 2023/2024 - Dian Puspitasari; Mochamad Guntur (Indonesian Journal of Integrated Science and Learning, 2024)
The completeness of science learning outcomes has an influence on the teacher's success in determining learning methods. Science learning about the human digestive system for class V students at SDN Simo, the level of completion of learning outcomes for students is only 52%. The aim of the classroom action research was to maximize science learning outcomes using the team quiz method assisted by animated video media on the human digestive system. The subjects in the research were fifth grade students, consisting of 10 female students and 13 male students. In cycle I, the percentage of completeness of student learning outcomes was 70% and increased by 13% in cycle II to 83%. The conclusion obtained from this research is that choosing a team quiz learning method using animated video media can maximize science learning outcomes for class V students at SDN 1 Simo